Refleksje nad kryzysami własnej tożsamości - Płużek, Zenomena (Horyzonty Wychowania, 2017)
It seems justified to affirm that man cannot know himselfcompletely. This truth has a great influence on considering andcomprehending his identity. Although people used to think thatidentity is based on the intellectual perception of one’s own personality,an equally essential factor appears the element of volition.It has to be emphasised that man constitutes the highestvalue for himself and for other people, for whom he should beresponsible. In this sphere, human identity crises arise. Talkingabout crises, then, one should look for the causes in the mistakenRefleksje nad kryzysami własnej tożsamościhierarchy of values and, finally, in the question: who am I? Thecrises, however, do not have to be entirely negative and that iswhy the author presumes the necessity of empirical investigationinto their origins.